Voltammetric analysis of ascorbic acid and its application in commercial roselle juices / Nur Syamimi Zainudin and Nur Anis Fadhilah Suib - Zainudin, Nur Syamimi; Suib, Nur Anis Fadhilah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Ascorbic acid is a water-soluble vitamin and commonly known as Vitamin C. Human cannot synthesize the ascorbic acid. It is naturally rich in citrus fruits and most of the vegetables. Hence, these fruits and vegetables become main source of ascorbic acid to meet the requirement of a dietary intake. The differential pulse anodic stripping voltammetric (DPASV) technique has been proposed for ascorbic acid analysis in commercial Roselle juices based on the electrochemical oxidation of the ascorbic acid at glassy carbon electrode (GCE). Phosphate buffer solution (PBS) at pH 5.0 was used as a supporting electrolyte